Inflammation--a lifelong companion. Attempt at a non-analytical holistic view - Ferencík, M; Stvrtinová, V; Hulín, I; Novák, M (Folia microbiologica, 2007)
Inflammation is a key component of the immune system. It has important functions in both defense and pathophysiological events maintaining the dynamic homeostasis of a host organism including its tissues, organs and individual cells. On the cellular level it is controlled by more than 400 currently known genes. Their polymorphisms and environmental conditions give rise to different genotypes in human population. Pro-inflammatory genotype, which dominates in the present population, may be advantageous in childhood but not in elderly people because it is characterized by an increased vulnerability to, and intensity of, inflammatory reactions. These reactions may be the possible reasons of chronic inflammatory diseases, especially in old age. Better understanding of complex molecular and cellular inflammatory mechanisms is indispensable for detailed knowledge of pathogenesis of many diseases, their prevention and directed drug therapy. Here we summarize the basic current knowledge on these mechanisms.
Keywords: obezita; signální transdukce; Immunity, Innate; Signal Transduction; kardiovaskulární nemoci; Humans; infekční nemoci; stárnutí; Inflammation; ateroskleróza; Genotype; lidé; Alzheimer Disease; Alzheimerova nemoc; Aging; zánět; Diabetes Mellitus, Type 2; Cardiovascular Diseases; Atherosclerosis; Neoplasms; nádory; genotyp; Obesity; Communicable Diseases; diabetes mellitus 2. typu; přirozená imunita